"Ain't No Rest for the Weary:" Continuing the Historical Legacy of Educational Praxis and Advocacy for Black Youth. (1st July 2018) - Benson, Richard D.
Abstract : This essay addresses the role of historical and socio-political nexus of educational praxis and advocacy in educating Black youth. The motivation for this work extends from the critical need of educators of Black youth to contextualize the general experiences of Black education as part of a greater trajectory of liberatory activism. By connecting the historical precedents of Black education, this essay also suggests that while the contemporary educational challenges of Black youth plague an ever changing national landscape, the methods of effectively addressing these deficiencies are historically rooted. Contemporary educational challenges for Black youth, which are the byproducts of neo-liberal agendas, can be addressed through deep historical analysis and by modeling many of the solutions-based methodologies of past generations.